Stock Investment Analysis Skills And Understanding Efficient Portfolio - Muhammad Habibullah Nur Ihsan; Muhammad Silmy Amjad; Bima Andhika Fernanda; Mohamad Bastomi (CV. AFDIFAL MAJU BERKAH, 2023)
Investment is the placement of some funds at this time with the hope of obtaining future profits. The fundamental thing in the investment decision process is to understand the relationship between the expected rate of return and the risk of an investment. The uncertainty of risk makes investors take a strategy to form a portfolio. Portfolio is a combination or combination or a set of assets, both in the form of real assets and financial assets owned by investors. Investors always want to maximise the expected return with a certain level of risk that they are willing to bear, or look for a portfolio that offers the lowest risk with a certain level of return in forming a portfolio. The characteristics of such a portfolio are referred to as an efficient portfolio. An investor needs to understand the meaning of investment, investment objectives, investment risk, and investment return. This study aims to introduce the Markowitz model in analysing the expected rate of return and its risks. The research method used in writing this article uses qualitative research with literature studies. From the discussion, it can be concluded that an investment portfolio can consist of several classes of the same asset or the same asset but consists of several different names. Investors can find out what stocks can be included in the optimal portfolio and the proportion of funds for each of these stocks formed by the Markowitz model